The Effects of NSAIDs on Patients Diagnosed with Gastroesophageal Reflux Disease (GERD) - Nurul Fauziah Rosandi; Rini Hendriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Non-Steroidal Anti-Inflammatory Drugs (NSAIDs) are a widely used class of medications for managing pain and inflammation. However, long-term use of NSAIDs has been associated with an increased risk of gastrointestinal disorders, including Gastroesophageal Reflux Disease (GERD). This study aims to analyze the impact of NSAID use on GERD patients based on recent research findings. The literature search was conducted through national and international databases such as Elsevier, Google Scholar, and the National Institutes of Health (NIH) National Library of Medicine, using keywords including GERD, NSAID, LES (Lower Esophageal Sphincter), gastric acid, reflux, and regurgitation. A total of 25 journal articles published between 2016 and 2024 were used as data sources. The findings indicate that NSAIDs inhibiting cyclooxygenase-1 (COX-1) can reduce prostaglandin production, which plays a protective role in the gastric mucosa, thereby increasing the risk of irritation and acid reflux. Conversely, selective COX-2 NSAIDs have a lower risk of gastrointestinal side effects, making them a safer alternative for patients with chronic pain and inflammation. This study highlights the importance of selecting the appropriate type of NSAID and monitoring its long-term use to minimize the risk of gastrointestinal disorders, particularly in patients with a history of GERD. By considering these factors, it is hoped that complications related to NSAID use in patients with digestive issues can be reduced.